Red, Gold and Green: Microbial Contribution of Rhodophyta and Other Algae to Green Turtle (Chelonia mydas) Gut Microbiome - Lucía Díaz-Abad; Natassia Bacco-Mannina; Fernando Miguel Madeira; Ester A. Serrao; Aissa Regalla; Ana R. Patrício; Pedro R. Frade (Microorganisms, 2022)
The fitness of the endangered green sea turtle (Chelonia mydas) may be strongly affected by its gut microbiome, as microbes play important roles in host nutrition and health. This study aimed at establishing environmental microbial baselines that can be used to assess turtle health under altered future conditions. We characterized the microbiome associated with the gastrointestinal tract of green turtles from Guinea Bissau in different life stages and associated with their food items, using 16S rRNA metabarcoding. We found that the most abundant (% relative abundance) bacterial phyla across the gastrointestinal sections were Proteobacteria (68.1 ± 13.9% “amplicon sequence variants”, ASVs), Bacteroidetes (15.1 ± 10.1%) and Firmicutes (14.7 ± 21.7%). Additionally, we found the presence of two red algae bacterial indicator ASVs (the Alphaproteobacteria Brucella pinnipedialis with 75 ± 0% and a Gammaproteobacteria identified as methanotrophic endosymbiont of Bathymodiolus, with <1%) in cloacal compartments, along with six bacterial ASVs shared only between cloacal and local environmental red algae samples. We corroborate previous results demonstrating that green turtles fed on red algae (but, to a lower extent, also seagrass and brown algae), thus, acquiring microbial components that potentially aid them digest these food items. This study is a foundation for better understanding the microbial composition of sea turtle digestive tracts.